Tingkat Partisipasi Masyarakat dalam Pemeliharaan Prasarana Dasar Permukiman di Kelurahan Samata - Amrullah Amrullah; Shirly Wunas; Mimi Arifin (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2021)
Housing facilities and basic infrastructures supply for community in Gowa Regency filled by various programs, such as Kota Tanpa Kumuh (Kotaku). This program aims to increasing basic infrastructure access and service in urban slum housing to support the implementation of livable, sustainable and productive urban housing, particularly in Kelurahan Samata. This research aims to identify the types of public participation, analyze the level of community participation and analyze the factors that affect the level of participation in maintenance base settlement in Kelurahan Samata by comparing two residential areas covered by the infrastructure improvement programs and residential areas that underserved environmental improvement program. This research was conducted on March to September 2020 in Kelurahan Samata. This research uses descriptive statistical analysis and simple linear regression analysis with SPSS 25. The result show that: 1) The form of public participation in two residential areas does not have a significant difference, is dominated by participation in the form of energy, each 51.92% and 50%; 2) Level of community participation in maintaining basic housing infrastructure in programmed areas is at level of citizen control participation, while in suburban areas with programs that are not implemented is at level of delegated power; and 3) Factor that affects level of participation in community by maintaining basic infrastructures on two residential areas using stepwise method on SPSS 25 affected by three variables, job, frequency, and motivation.